The Effect of the Picture and Picture Method on Improving Narrative Text Writing Skills in Elementary School Students - Amalia Putri Rahayu; Dede Permana; Eva Astuti Mulyani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to determine the effect of the Picture and Picture method on the narrative text writing ability of fourth-grade students at SD Negeri 106 Pekanbaru. This study was motivated by the low ability of students in writing narrative texts, especially in constructing a coherent storyline, developing characterization and setting, and using language in accordance with linguistic rules. The study was conducted at SD Negeri 106 Pekanbaru involving 20 students as research subjects. The research method used was a quantitative method with a pre-experimental design of the One Group Pretest–Posttest Design type. The research instruments used included observation sheets, writing tests in the form of pretests and posttests, and documentation of students’ writing results. Assessment of narrative text writing ability focused on aspects of text structure and language use. The learning process was carried out by applying the Picture and Picture method, namely students observed, sorted, and arranged images based on certain themes as a basis for developing story ideas. The data obtained were analyzed using a t-test to determine differences in students’ narrative text writing ability before and after being given treatment. The results of the study showed an increase in the average score of students’ narrative writing skills, from 48.50 in the pretest to 60.63 in the posttest. The analysis showed that the Picture and Picture method was effective in improving the narrative writing skills of fourth-grade students at SD Negeri 106 Pekanbaru.